Perceptions with Non-English Educational Background Competence in English Teaching - Andi Mukarramah Nagauleng; Andi Asrifan; Ahmad Mustamir Waris (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research's purposes were: (1) exploring the perceptions of non-English teachers in teaching English at IAIN Manado; (2) assessing the ability of non-English teachers to attain IAIN Manado student qualifications. This study uses a mixed research method based on an exploratory sequence. The research was conducted using IAIN Manado Purposive sampling technique, and the researcher determined the research object by specific criteria. The study results show: (1) They loved how a non-English professor teaches English. They say that if a non-English teacher is amiable in teaching, he often motivates students to learn English. They also value non-English-based lecturers. Students also actively follow teaching and learning activities, (2) Student evaluations also were found in pre-test and post-test data when post-test ratings were increased, with 7 (41.17%) having an average value, 5 (29.42%) with good ratings, 4 (23.0%) with poor scores, and 1 (5.89%) with very good ratings. This means a significant increase in English language learning by non-English lecturers.